The Scars We Carve : Bodies and Wounds in Civil War Print Culture - Johnson, Allison M., 1984- (Book collections on Project MUSE., 2019)
"In The Scars We Carve: Bodies and Wounds in Civil War Print Culture, Allison M. Johnson uncovers the ubiquitous images of bodies--white and black, male and female, solider and noncombatant--that appear throughout newspapers, lithographs, poems, tales, and other texts circulated during and in the decades immediately following the Civil War. These images underscore the extent to which the violence and destruction of the internecine conflict marked the physical bodies of American citizens and the geographic and symbolic bodies of the American republic. In contrast to narratives of the Civil War that stress ideological abstraction, disembodiment, and reconciliation, Johnson shows that the era's print culture contains a literary and visual record of the war that is embodied and individualized. She finds this record inscribed on the pages of newspapers and journals, in the left-handed writing of recent amputees, and in the words of little-read and rarely anthologized amateur poets and storytellers. Throughout this innovative study, Johnson underscores how American citizens interacted with and represented the physical effects of war to create a literary record permeated by corporeality and suffering"--